EDUKASI PENCEGAHAN PERUNDUNGAN DI SDN 1 CIBADAK KECAMATAN CIBADAK KABUPATEN LEBAK - BANTEN - Ende, Ende; Kurnia, Ela; Syahriar, Ferdi Rizki; Sari, Dewi Nurmala (MAJU : Indonesian Journal of Community Empowerment, 2024)
Bullying in primary schools is a serious problem that can negatively affect children's development. To overcome this problem, effective socialisation is needed in the school environment. This article reports on a community service activity in the form of bullying socialisation held at SDN 1 Cibadak, with 50 students participating. This activity aims to increase students' understanding of the dangers of bullying, its types, and how to prevent it. The results of the activity showed a significant increase in students' understanding, which was analysed through survey data and presented in tabular form.